The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1002/gj.2458
|View full text |Cite
|
Sign up to set email alerts
|

Geochemistry and petrogenesis of the Late Cretaceous Haji‐Abad ophiolite (Outer Zagros Ophiolite Belt, Iran): implications for geodynamics of the Bitlis–Zagros suture zone

Abstract: The Haji‐Abad ophiolite in SW Iran (Outer Zagros Ophiolite Belt) is a remnant of the Late Cretaceous supra‐subduction zone ophiolites along the Bitlis–Zagros suture zone of southern Tethys. These ophiolites are coeval in age with the Late Cretaceous peri‐Arabian ophiolite belt including the Troodos (Cyprus), Kizildag (Turkey), Baer‐Bassit (Syria) and Semail (Oman) in the eastern Mediterranean region, as well as other Late Cretaceous Zagros ophiolites. Mantle tectonites constitute the main lithology of the Haji… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(7 citation statements)
references
References 121 publications
0
7
0
Order By: Relevance
“…Given its structural position below subducted units (oceanic and offscraped from the slab or as part of a forearc, i.e., the Seghin and Ashin units, respectively; Angiboust et al, 2016), it can be concluded that Siah Kuh was located outboard of Eurasia, as part of the lower plate with respect to the Eurasian subduction zone. The presence of boninites (Moghadam et al, 2013) suggests that the Siah Kuh seamount was also in a supra-subduction position with respect to a second, more southerly subduction (which is well documented by regional studies; e.g., Searle and Cox, 1999;Agard et al, 2006Agard et al, , 2007. Due to its structural position below the Ashin unit and the Seghin blueschists, the Siah Kuh unit most likely underwent subduction and metamorphism after them.…”
Section: Regional Significancementioning
confidence: 79%
See 3 more Smart Citations
“…Given its structural position below subducted units (oceanic and offscraped from the slab or as part of a forearc, i.e., the Seghin and Ashin units, respectively; Angiboust et al, 2016), it can be concluded that Siah Kuh was located outboard of Eurasia, as part of the lower plate with respect to the Eurasian subduction zone. The presence of boninites (Moghadam et al, 2013) suggests that the Siah Kuh seamount was also in a supra-subduction position with respect to a second, more southerly subduction (which is well documented by regional studies; e.g., Searle and Cox, 1999;Agard et al, 2006Agard et al, , 2007. Due to its structural position below the Ashin unit and the Seghin blueschists, the Siah Kuh unit most likely underwent subduction and metamorphism after them.…”
Section: Regional Significancementioning
confidence: 79%
“…We consider hypothesis 3 to be the most likely, because isostatic equilibration of the lithosphere under the load of a seamount is very fast (<1 m.y., Campbell, 1986) and expected to be of the order of several kilometers (e.g., Hawaii, Watts and ten Brink, 1989). The boninites reported in Siah Kuh (Moghadam et al, 2013) also point to an intra-oceanic (and supra-subduction) setting.…”
Section: Record Of Subsidence In the Siah Kuh Seamountmentioning
confidence: 93%
See 2 more Smart Citations
“…Boninites are common in nearly all of the Late Cretaceous Neotethyan ophiolites as well as the Zagros Inner and Outer Belt ophiolites. These rocks are essentially found in fore-arc environments such as in the IBM fore-arc region (Shafaii Moghadam et al, 2013). (Bridges et al, 1995).…”
mentioning
confidence: 99%